Public Perceptions of Current COVID-19 Vaccinations. Results of a Pilot Survey. (December 2021) - Kantarcioglu, Bulent; Patel, Krishan; Lewis, Joseph; Iqbal, Omer; Siddiqui, Fakiha; Jabeen, Nusrat; Laddu, Atul R.; Carter, Charles A.; Fareed, Jawed
Introduction: We conducted a cross-sectional survey as a part of an educational program in collaboration with the Global Thrombosis Forum (GTF), an affiliate of North American Thrombosis Forum (NATF), and Loyola University about public perceptions of COVID-19 and COVID-19 vaccinations in the US. In this study, we are reporting the results of this survey. Materials and Methods: The survey, in the form of a questionnaire, has been developed by GTF and faculty members. A prepared questionnaire was sent to the members of the Georgia and Illinois communities. Results: In our current study, the COVID-19 vaccine willingness rate was 94.5% and vaccination rate was 90.9%. In multivariate analysis believing to have enough information about the safety and efficacy of COVID-19 vaccines (OR: 3.730, 95% CI: 1.199–11.603, p: 0.023) and gender (OR: 0.123, 95% CI: 0.016–0.967, p: 0.046) were significant predictors for vaccine willingness. Previous COVID-19 infection (OR: 0.215, 95% CI: 0.061–0.758, p: 0.017), moderate and severe effects of COVID-19 pandemic on participant's life (OR: 4.631, 95% CI 1.681–12.760, p: 0.003) and believing to have enough information about the safety and efficacy of COVID-19 vaccines (OR: 4.119, 95% CI: 1.508–11.253, p: 0.006) were significant predictors for final vaccination status. Conclusion: In conclusion, currently vaccination remains one of the most effective tools in the fight against the COVID-19 pandemic. The vaccine hesitancy is a complex phenomenon that is driven by individuals' perceptions of safety, and efficiency of the vaccines. We must continue to educate the public and communities that vaccines are safe, that they are effective and that they are still required even after a COVID-19 infection.